Tailoring neoadjuvant chemotherapy for a pregnant patient diagnosed with IB2 squamous cervical carcinoma - Anna Babkova; Helena Robova; Hana Malikova; Jana Drozenova; Tomas Pichlik; Michael J. Halaska; Lukas Rob (Elsevier, 2024)
The incidence of cancer during pregnancy is steadily rising because of the postponement of plans for childbearing. One of the most common cancers diagnosed during pregnancy is cervical cancer. Diagnosis of most cases usually occurs in the early stages, but there are still cases of tumors staged IB2 and higher. In these cases, the treatment strategy entails administration of neoadjuvant chemotherapy. However, a universally recognized standardized regimen for neoadjuvant chemotherapy treatment of cervical cancer during pregnancy has yet to be established. The chemotherapy agents used during treatment are known for their fetal adverse effects. The aim of the therapy is to attain full-term pregnancy while minimizing fetal toxicity and decreasing tumor size. In this case report, we present a first-time sequential chemotherapy administration to minimize the cumulative toxicity of individual regimens and demonstrate the benefits for the patient and fetus.